IMPLEMENTASI EKONOMI KERAKYATAN BERBASIS EKONOMI DIGITAL UNTUK MEMBANGKITKAN UMKM PADA MASA PANDEMI COVID 19 - Mada Angga Dwi Nata; Haryono Haryono (PROMOSI (Jurnal Pendidikan Ekonomi), 2022)
The COVID-19 pandemic has forced the public to implement health protocols to reduce the number of COVID-19 spreads. The impact of the COVID-19 pandemic has forced MSME actors to be able to survive with this condition. Many MSME actors who cannot survive in this condition have gone out of business. However, some MSMEs have more ideas that can be used as solutions to overcome problems during a pandemic. This solution is expected to make MSME actors able to rise during the pandemic. MSMEs that act as the foundation of the people's economy can create a digital-based economy in their application. Based on the results of the research conducted, it is concluded that the role of MSMEs as a people's economy can be the mainstay of the community in a pandemic condition. MSMEs that can survive during the COVID-19 pandemic are using online marketing (digital marketing) to increase sales during the COVID-19 pandemic.Keywords: digital economy, people's economy, UMKM